TEACHING READING NARRATIVE TEXT THROUGH ANCHORED INSTRUCTION STRATEGY TO THE EIGHTH GRADE STUDENTS OF STATE JUNIOR HIGH SCHOOL 46 OF PALEMBANG - Riza Yoga Indriani (Esteem Journal of English Education Study Programme, 2020)
Abstract: The main purpose of this study was to find out whether or not there was any significant difference between students who taught by using Anchored Instruction Strategy to the eighth grade students of State Junior High School 46 of Palembang. This research was conducted by using quasi-experimental design, that is, pretest posttest non equivalent control group design that compare 2 groups of the students. The population consisted of 276 students from the eight classes of State Junior High School 46 of Palembang in academic year 2017/2018. The sample of the study was selecting by purposive sampling involving 62 students as the sample. Thirty one students were in the experimental group and thirty one students in the control group. To collect the data, a written test in multiple choice was used. The written test was administered twice as pretest and posttest. the result of the test analyzed by using t-test (paired sample t-test and independent sample t-test. In this study, the value of t-obtained was higher than the value of t-table (7.93 > 1.697) consequently the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. In conclusion, the use of Anchored Instruction Strategy was effective in teaching reading of the eighth grade students in improving reading comprehension achievement, particularly narrative paragragph.